A cytological and molecular analysis of D-genome chromosome retention following F2–F6 generations of hexaploid × tetraploid wheat crosses - Padmanaban, Sriram; Zhang, Peng; Sutherland, Mark W; Knight, Noel L; Martin, Anke (Crop and pasture science, 2018)
Both hexaploid bread wheat (AABBDD) (Triticum aestivum L.) and tetraploid durum wheat (AABB) (T. turgidum spp. durum) are highly significant global food crops. Crossing these two wheats with different ploidy levels results in pentaploid (AABBD) F1 lines. This study investigated the differences in the retention of D chromosomes between different hexaploid × tetraploid crosses in subsequent generations by using molecular and cytological techniques. Significant differences (P < 0.05) were observed in the retention of D chromosomes in the F2 generation depending on the parents of the original cross. One of the crosses, 2WE25 × 950329, retained at least one copy of each D chromosome in 48% of its F2 lines. For this cross, the retention or elimination of D chromosomes was determined through several subsequent self-fertilised generations. Cytological analysis indicated that D chromosomes were still being eliminated at the F5 generation, suggesting that in some hexaploid × tetraploid crosses, D chromosomes are unstable for many generations. This study provides information on the variation in D chromosome retention in different hexaploid × tetraploid wheat crosses and suggests efficient strategies for utilising D genome retention or elimination to improve bread and durum wheat, respectively.